2013
DOI: 10.1016/j.fertnstert.2013.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Fertility drug use and the risk of ovarian tumors in infertile women: a case-control study

Abstract: Objective To assess the influence of infertility and fertility drugs on risk of ovarian tumors. Design Case-control study (Mayo Clinic Ovarian Cancer Study). Setting Ongoing academic study of ovarian cancer. Patient(s) A total of 1900 women (1028 with ovarian tumors and 872 controls, frequency matched on age and region of residence) who had provided complete information in a self-report questionnaire about history of infertility and fertility drug use. Intervention(s) None Main outcome measure(s) Eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 25 publications
(31 reference statements)
2
34
0
1
Order By: Relevance
“…In our previous study, we found higher risk of ovarian cancer in women with primary infertility and those conceiving only one child (23). On the other hand, several other studies observe no increase in risk of ovarian cancers (3941), and/or no difference in risk between nulliparous and parous women with fertility treatment (20, 41). …”
Section: Discussionmentioning
confidence: 89%
“…In our previous study, we found higher risk of ovarian cancer in women with primary infertility and those conceiving only one child (23). On the other hand, several other studies observe no increase in risk of ovarian cancers (3941), and/or no difference in risk between nulliparous and parous women with fertility treatment (20, 41). …”
Section: Discussionmentioning
confidence: 89%
“…This would seem to be a particular concern for women who are not anovulatory, as the stimulation would occur against a backdrop of incessant ovulation. In the current article (1), neither infertility nor infertility drug use were associated with increased risk of ovarian tumor. Whereas statistical power was modest, the study had the power to detect an effect for infertility and infertility drug use well below a risk of 2.0, which is in range of several previous reports.…”
mentioning
confidence: 60%
“…The article by Dr. Asante and colleagues (1) in the current issue attempts to address the question whether or not infertility drugs increase ovarian tumor risk. This is a question of great interest to the reproductive health community—but it is not a simple question and the data to provide a clear answer appear elusive.…”
mentioning
confidence: 99%
“…Results from two recent case-control studies conducted in the United States provide further evidence that fertility drug use does not significantly contribute to risk of ovarian cancer among the majority of women when adjusting for known confounding factors [48*,49*]. Both studies observed no association between fertility drug use and overall risk of ovarian cancer.…”
Section: Recent Studiesmentioning
confidence: 99%
“…Both studies observed no association between fertility drug use and overall risk of ovarian cancer. Kurta et al used data from the Hormones and Ovarian Cancer Prediction (HOPE) study [48*]; Asante et al used data from the Mayo Clinic Ovarian Cancer study [49*]. Strengths of both studies include a relatively large sample size and the availability of detailed reproductive and medical histories of study participants.…”
Section: Recent Studiesmentioning
confidence: 99%